2019
DOI: 10.1038/s41467-019-13504-8
|View full text |Cite
|
Sign up to set email alerts
|

Fast and quantitative 2D and 3D orientation mapping using Raman microscopy

Abstract: Non-destructive orientation mapping is an important characterization tool in materials science and geoscience for understanding and/or improving material properties based on their grain structure. Confocal Raman microscopy is a powerful non-destructive technique for chemical mapping of organic and inorganic materials. Here we demonstrate orientation mapping by means of Polarized Raman Microscopy (PRM). While the concept that PRM is sensitive to orientation changes is known, to our knowledge, an actual quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 69 publications
2
40
0
Order By: Relevance
“…LP anisotropy becomes significant for input polarization components, which differ from 0° and 90°. [ 34 ] Polarization simulation analysis also shows that this effect takes place at the edges of the line. However, polarization artifacts are at the level of a few degrees and can thus be neglected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LP anisotropy becomes significant for input polarization components, which differ from 0° and 90°. [ 34 ] Polarization simulation analysis also shows that this effect takes place at the edges of the line. However, polarization artifacts are at the level of a few degrees and can thus be neglected.…”
Section: Resultsmentioning
confidence: 99%
“…However, the control of the laser polarization state becomes a challenging task when the angle of linear polarization differs from 0° and 90° with respect to the coordinate system shown in Figure 1a. [ 34 ] In Figure S3, Supporting Information, we present polarization simulation results obtained in Zemax Optics Studio for the laser polarization propagation after beam reflection from mirrors. Simulation was performed at three different input polarization angles: 0°, 90°, and 45° for linear polarization (Figure S3b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…It can be used to explore or improve the properties of the material based on their grain structures. [ 40 ] In Figure , the Raman mapping is carried out to study the spatial distributions within the area circled by the white box shown in Figure 1b. This 2D Raman mapping spectroscopy consists of automated stage, which can offer a fast‐scanning confocal Raman microscopy, and a step of 100 nm is used to enable the system to produce the 2D Raman mapping with a high confocality.…”
Section: Resultsmentioning
confidence: 99%
“…Combined SHG and Raman microscopies have been used to reveal structures of thymine crystals in this paper and this constitutes a unique approach for molecular crystal characterization. This is a step ahead compared to a single Raman microscopy techniques 21,38,39 . The Raman signal does not require macroscopic ordering, consequently, the generated signal from a crystalline sample will necessarily contain a background from noncrystalline phase.…”
Section: Discussionmentioning
confidence: 99%
“…The CARS signal originates from the vibrational signature of the material that is connected to the structure of the chemical bonds. To identify the relationship between the structure and properties of the material, the effectiveness of orientational mapping using polarized Raman 21 or CARS 22 , 23 microscopy was demonstrated. While the techniques have long history in material research, the bulk nonlinear optical studies of thymine to date 24 27 were not able to distinguish the different polymorphs of thymine crystals.…”
Section: Introductionmentioning
confidence: 99%